Reprint of: Recent Updates on Obesity Treatments: Available Drugs and Future Directions. (1st November 2020) - Dragano, Nathalia R.V.; Fernø, Johan; Diéguez, Carlos; López, Miguel; Milbank, Edward
Highlights: The prevalence of obesity has risen dramatically worldwide over the last decades. Overweight and obesity are major risk factors for numerous comorbidities. Currently, bariatric surgery is the most effective way to induce body weight loss. The FDA-approved anti-obesity drugs are few and their efficiency remains limited. Promising pharmacotherapies targeting CNS and combining different mechanisms to induce body weight loss are in development. Abstract: In the last thirty years, obesity has reached epidemic proportions and is now regarded as a major health issue in contemporary society trending to serious economic and social burdens. The latest projections of the World Health Organization are alarming. By 2030, nearly 60% of the worldwide population could be either obese or overweight, highlighting the needs to find innovative treatments. Currently, bariatric surgery is the most effective way to efficiently lower body mass. Although great improvements in terms of recovery and patient care were made in these surgical procedures, bariatric surgery remains an option for extreme forms of obesity and seems unable to tackle obesity pandemic expansion. Throughout the last century, numerous pharmacological strategies targeting either peripheral or central components of the energy balance regulatory system were designed to reduce body mass, some of them reaching sufficient levels of efficiency and safety. Nevertheless, obesity drug therapy remains quite limited on its effectiveness to actually overcome the obesogenic environment. Thus, innovative unimolecular polypharmacology strategies, able to simultaneously target multiple actors involved in the obesity initiation and expansion, were developed during the last ten years opening a new promising avenue in the pharmacological management of obesity. In this review, we first describe the clinical features of obesity-associated conditions and then focus on the outcomes of currently approved drug therapies for obesity as well as new ones expecting to reach the clinic in the near future.